The Language of Mystics - the Mystics of Language. A Reading of Kabir’s Poem - Piekarski, Przemysław (Acta Orientalia Vilnensia, 2001)
The paper tries to solve one of many Kabir’s mysteries - his ontological outlook. Being suspended between Hinduism and Islam, the great mystic gives in his poetry hints which can be read twice-fold. Linguistic analysis of one of his poems sets to dislose monistic and dualistic attitudes to the Absolute.